Kepastian Hukum Bagi Tenaga Kesehatan dalam Kasus Malpraktik Akibat Pelanggaran Jam Kerja : Tanggung Jawab dan Perlindungan Hukum - Kevin Stevanus Jeremia; Abdul Rahman Maulana Siregar (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This journal discusses legal certainty for healthcare workers in cases of malpractice resulting from violations of working hours. The primary focus of this study is to identify the legal responsibilities that can be imposed on healthcare workers and the legal protections available to them. Through an analysis of regulations under Law No. 17 of 2023, the article finds that although a clear legal framework exists, challenges remain in its implementation. The study also highlights the importance of transparent and fair resolution procedures to protect the rights of healthcare workers and patients. Therefore, collaborative efforts between the government, professional organizations, and healthcare institutions are needed to create a safe and supportive work environment.